Sobrecarga do cuidador informal da pessoa idosa frágil: uma revisão sistemática - Raquel Souza Azevedo (2010)
Population aging is a phenomenon observed throughout the world today. Brazil isexperiencing a fast aging of its population, due to the reduction in fertility rates andmortality and the epidemiological shift of the infectious diseases overlap, maternaland perinatal causes for chronic diseases and external causes. The chronic anddegenerative diseases directly affect elderlys quality of life, making them fragileand vulnerable. One of the weaknesses that most compromise the independenceand autonomy of the elderly is cognitive impairment, i.e., loss of cognition,behavioral changes and impairment of basic activities of the daily living, leading tothe need of a caregiver. Due to the lack of professionals - formal caregivers - andalso to the socioeconomic conditions of the population, care is frequently providedby a family member - informal caregiver. This person assumes a role for which heis not prepared, causing a physical and emotional burden. The need of evidencesof this burden led to the development of this study, aiming to compare the physicaland emotional burden of informal caregivers of frail elderly people with and withoutdementia, through a systematic literature review. The following databases wereresearched: LILACS, MEDLINE/BVS, PubMed, CINAHL, BDENF and IBECS,using descriptors and terms. Only two articles comparing caregivers burdenthrough a descriptive study were identified. The articles were developed inEngland, published in 2002, and in the U.S., published in 2008. The two articlesconclusion was that the physical and emotional burden of the informal caregiversof a frail elderly person with dementia is greater than the caregiver of those withoutdementia. According to the classification adopted the level of evidence for thisconclusion was V. Therefore, it becomes urgent to develop researches on theinformal caregiver, seeking to point out their needs and ways to minimize theiremotional and physical burdens arising from the care of the frail elderly.